Study of the impact of green finance reform and innovation pilot zones on total-factor carbon productivity in Chinese cities - Zhang, Youzhi; Bian, Rumeng; Liu, Yinke; Wang, Jingyi; Zhao, Jing (Frontiers in Environmental Science, 2025)
With global climate change, environmental pollution, and other problems becoming increasingly prominent, realizing the green development of the economy has become an urgent issue for most countries. On the basis of the panel data of 282 cities in China from 2012 to 2022, an SBM-GML model is first applied to measure the total factor carbon productivity of cities; then, green financial reform and innovation pilot zones are established as a quasi-natural experiment, and a multi-period DID method is adopted to test the impact of green financial reform and innovation pilot zones on the total factor carbon productivity of cities in stages. The study reveals that (1) urban total factor carbon productivity can be significantly increased through the construction of green financial reform and innovation pilot zones, and this finding is robust; (2) the heterogeneity test reveals that the construction of green financial reform and innovation pilot zones can significantly increase total factor carbon productivity in the eastern, central and western regions, with the effect being more obvious in the western region; and (3) a mechanism test reveals that the construction of green financial reform and innovation pilot zones can enhance urban total factor carbon productivity by improving the level of green innovation and promoting the ecological industrial structure, whereas public environmental concern can effectively enhance the policy effect of green financial reform and innovation pilot zones on urban total factor carbon productivity. On the basis of the research findings, this paper provides a reliable reference for other countries hoping to implement green finance policies to realize low-carbon sustainable development and improve total factor carbon productivity.